Intramural Intestinal Metastasis of Malignant Melanoma as a Rare Cause of Ileoileal Intussusception: A Case Report and Review of the Literature - Gary Amseian; Alexandre Soler; Alba Torroella; Lia Sisuashvili; Paula Escarcena; Gerard Rafart (Case Reports in Surgery)
Intussusception in adults is rare and poses a diagnostic challenge, often due to neoplastic causes. Metastatic melanoma is known to spread to the gastrointestinal tract, especially the small intestine. We report the case of a patient with obstructive symptoms and a history of metastatic melanoma. An emergency abdominal computed tomography (CT) scan identified an obstruction caused by ileoileal intussusception located at the site of a previously described enteric metastasis. Following palliative surgery with ileal resection, two nodular lesions causing intussusception were identified, and pathological examination confirmed intramural metastases from melanoma. In adult patients with obstructive symptoms and a history of melanoma, intussusception secondary to intestinal metastases should be considered in the differential diagnosis.